The Influence of Service Quality and Customer Relationship Management on Customer Loyalty with Satisfaction as an Intervening Variable at Bank Syariah Indonesia KC Southeast Aceh - Sukma, Novita Riyati; Sugianto, Sugianto; Nurbaiti, Nurbaiti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to evaluate and analyze the influence of customer satisfaction on loyalty at Bank Syariah Indonesia (BSI) KC Southeast Aceh. This study utilizes a quantitative research methodology. The study covered all branches of Bank Syariah Indonesia (BSI) in Southeast Aceh, totaling roughly 34,754 branches. The response criteria evaluated were banks that had employed the services of Bank Syariah Indonesia (BSI) KC Southeast Aceh for at least two years. The sample size was increased to incorporate 100 responders. The study utilizes the Partial Least Square (PLS) method for data analysis, making use of the SmartPLS v software. 4.1.0 as a tool. PLS-SEM is an adapted iteration of the structural equation modeling (SEM) methodology. The data analysis methods employed in this study encompass Descriptive Analysis, Structural Equation Modeling (SEM) Analysis, and Partial Least Squares (PLS). Structural model evaluation entails the assessment of R-square (R2) and F-square (F2) values, together with the examination of indirect effects and the conduct of hypothesis testing. In addition, a SEM analysis is conducted, taking into account intervening variables. The research findings suggest that there is no discernible relationship between the quality of service provided and the loyalty of clients. CRM has little influence on client loyalty. The level of service provided significantly influences customer happiness. CRM has no discernible effect on satisfaction. client satisfaction can serve as a mediator in the connection between service quality and client loyalty. The correlation between customer relationship management (CRM) and client loyalty is unaffected by satisfaction. Satisfaction has a significant influence on customer loyalty.